Efficacy of an Immune Modulator in Experimental <emph>Chlamydia trachomatis</emph> Infection of the Female Genital Tract (Hindawi Limited, 2006)
<emph>Objective.</emph> The aim of this study was to determine if vaginal application of the immune response modifier imiquimod (Aldara cream, 3M Pharmaceuticals, St Paul, Minn) would alter the course and/or outcome of female genital tract infection with a human isolate of <emph>Chlamydia trachomatis</emph> in a murine model. <emph>Methods.</emph> Groups of CF-1 mice were treated with Aldara on three different schedules: (1) ongoing beginning 5 days prior to and continuing through day 5 of infection; (2) a single prophylactic dose 2 hours prior to infection; and (3) therapeutic from day 4 to day 14 of infection. Mice were infected vaginally with a serovar D strain of <emph>C trachomatis</emph>, and monitored by culture to determine the level of shedding and duration of infection. <emph>Results.</emph> We observed a significant reduction in both duration of infection and the level of shedding during the acute phase in mice treated on an ongoing basis commencing 5 days prior to infection. There was no effect with respect to the other regimens. <emph>Conclusion.</emph> These results demonstrate that ongoing Aldara treatment has efficacy and may enhance local innate immunity which reduces the duration of subsequent infection with human isolates of <emph>C trachomatis</emph> in a murine model of female genital tract infection.